Factors Related To The Occurrence Of Diarrhea In Children In River Village Lala Work Area Health Lala River District Indragiri Hulu - Fentia, Lia; Andriyani, Desi Nasea (Journal of Global Research in Public Health, 2018)
Diarrheal disease is a leading cause of death in children under five,There are several factors that cause diarrhea one’s behavior. Based on data from 18 health centers in Indragiri Hulu in 2016, one of the health centers with the highest incidence of diarrhea was obtained 110 health centers Lala River toddler has diarrhea of â€‹â€‹a total of 419 infants with the highest cases in Sungai Lala there were 36 cases. This study aims to determine the factors associated with the incidence of diarrhea in infants in Sungai Lala Lala River Region Public Health Center Indragiri Hulu. This type of quantitative research with cross sectional approach.The study was conducted in Sungai Lala,Mechanical sampling total sampling,Samples of this study amounted to 57 respondents. Data were analyzed by univariate and bivariate.The results showed 70.2% children did not experience diarrhea, as many as 80.7% were exclusively breastfed, the majority of the use of a bottle of milk for infants was 66.7%, more mothers who have poor hand washing habits 40.4% and the majority of clean water is contaminated with 68.4% of respondents. The results of chi square test found no relation of exclusive breastfeeding (p = 0.068) and using contaminated water (p = 0.481) and the incidence of diarrhea in infants. An association use of the bottle (p = 0.019) and handwashing (p = 0.006) and the incidence of diarrhea in infants. It is expected that the mother to be able to maintain the cleanliness of hands before touching food or before feeding infants and use hygienic milk bottles to prevent diarrhea in infants.